Prison Nurses' Professional Identity. Issue 3 (July 2019) - Goddard, Donna; de Vries, Kay; McIntosh, Tania; Theodosius, Catherine
Abstract : ABSTRACT: In the United Kingdom, health and justice services nurses are a diverse group working across a range of contexts and settings such as police custody, sexual assault referral centers, young offenders' institutes, and prisons and probation. Recruitment and retention to the specialist field of health and justice services nursing, specifically prison nursing, is problematic in the United Kingdom. In this article, we consider the background to the current situation in prison nursing and summarize some of the existing literature and research relating to this specialty to raise, for discussion and debate, issues that are pertinent to the concept of professional identity and professionalism. Role definition, resilience and burnout, and education within prison nursing are identified in relation to the development of professional identity. It could be that professional identity is the missing link to recruitment and retention.